2009
DOI: 10.1002/ange.200806187
|View full text |Cite
|
Sign up to set email alerts
|

Towards Photocatalytic Alkane Oxidation: The Insertion of Dioxygen into a Platinum(II)–Methyl Bond

Abstract: The selective catalytic oxidation of methane and higher alkanes remains one of the great challenges in catalysis research. Considerable progress has been made during the last three decades regarding the CÀH activation of alkanes, in particular electrophilic activation reactions with late transition metals. [1][2][3][4] Once C À H bond cleavage has occurred at a metal center, a functionalization of the metal-carbon bond is required, followed by release of the product and regeneration of the catalyst. In the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…There have only been two previously reported Pt− OOCH 3 solid-state structures. 10,12 Compared to these structures, the Pt−O bond length of 3-t Bu is of similar length at 1.985(8) Å, as is the O−O bond length (1.419(10) Å).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…There have only been two previously reported Pt− OOCH 3 solid-state structures. 10,12 Compared to these structures, the Pt−O bond length of 3-t Bu is of similar length at 1.985(8) Å, as is the O−O bond length (1.419(10) Å).…”
mentioning
confidence: 84%
“…However, mechanistic studies of these systems did not support a radical chain mechanism. 12,13 Although an experimental article proposed a mechanism where excited triplet-state dinuclear intermediates are generated upon exposure to light and then undergo reaction with O 2 to form the M−OOCH 3 species, 13 a recent computational paper has suggested that the reaction proceeds instead through a triplet-state excited monomer that reacts with oxygen to form superoxo and peroxo intermediates on their way to the M−OOCH 3 products. 14 With such a small number of reported examples of oxygen insertion into M−C bonds, it is difficult to generalize or make predictions concerning the potential reactivity of other late metal alkyl complexes with oxygen.…”
mentioning
confidence: 99%
“…Britovsek et al. reported the insertion of O 2 into the PtMe bond of the cationic, amino‐substituted terpyridine complex [( (NH 2) 2terpy)PtMe][SbF 6 ] ( 83 , (NH 2) 2terpy=6,6′‐diaminoterpyridine, Scheme ) to form [( (NH 2) 2terpy)PtOOMe][SbF 6 ] ( 84 ), which was crystallographically characterized 108. Notably the reaction did not proceed when a complex with an unsubstituted terpyridine ligand, [(terpy)PtMe][SbF 6 ], was used.…”
Section: Stoichiometric Reactions Of Ptii With O2mentioning
confidence: 99%
“…In addition to selective Pt–C fluorination reactions, we have also initiated efforts to couple cyclization with Pt–C oxygenation schemes to access C3-oxygenated polycycles. Partial success in achieving this goal was realized by a strategy that intercepts the Pt-alkyl intermediate with a 1-electron oxidant to form a Pt­(III)-alkyl. The chemistry of such species has previously been examined by Kochi, Trogler, Baird, and others and is characterized by rapid Pt/Pd–C bond homolysis to reform the divalent state (in a form suitable for initiating the COR) and a free radical.…”
Section: Pt–c Bond Functionalizationsmentioning
confidence: 99%